Desain dan Simulasi Dual Input Single Output Buck Converter dengan Kontrol Fuzzy - Abdul Rahman Wachid; Endro Wahjono; Syechu Dwitya Nugraha Nugraha (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2021)
In this paper, a dual input single output buck converter with fuzzy control is designed and simulated for a DC load supply using the PSIM software. The dual input single output buck converter can work with two different sources. The use of the two power sources of photovoltaic and wind turbine is an alternative solution for obtaining a greater rated power to supply DC loads. The solar panel and the wind turbine will supply the power for the dual input buck converter circuit simultaneously. For the two power sources to work simultaneously, the duty cycle is set using fuzzy control, so that the output voltage can match the desired voltage. Simulation testing is carried out with photovoltaic conditions with varying irradiation and temperature values, as well as varying wind speeds in the wind turbine, i.e, between 4-8 m/s. The simulation results show that the dual-input single-output buck converter can work when powered by two different power sources with a stable output voltage of the converter at its set point, i.e., 14.4 volts.